A COMPARATIVE DERMAL MICRODIALYSIS STUDY OF DICLOFENAC QPS VERSUS CONVENTIONAL 1% DICLOFENAC GEL (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
The study was designed to evaluate penetration of diclofenac through skin after application of diclofenac 4 % quick penetrating solution (Dynapar QPS) versus conventional diclofenac 1% gel. In this 2 way crossover study, 6 male healthy human subjects were randomized to receive either 1 mg of diclofenac of the Dynapar QPS (25µl) or 1 mg of diclofenac from gel (100 mg) on to the marked area of the forearm three times daily for 3 days. On day 4, after 10th application, the dermal microdialysis was performed. The dialysate samples were collected every half an hour for 6 hours and diclofenac concentration was determined. Mean (± SD) Cmax after administration of Dynapar QPS was significantly higher as compared to diclofenac gel (11.10 ± 5.18μg/mL versus 2.34 ± 2.84 respectively, P = 0.0058). The time to reach Cmax was also lesser with Dynapar QPS as compared to diclofenac gel (1.5 ± 0.0 hrs versus 2.17 ± 1.29 respectively, P = 0.2617). The mean AUC0–t and AUC0-∞ after administration of Dynapar QPS was significantly higher as compared to Diclofenac gel (AUC0–t: 9.48 ± 4.76 hr.ng/mL versus 3.53 ± 4.22 respectively, P = 0.0125; AUC0-∞ : 10.82 ± 5.03 hr.ng/mL versus 4.74 ± 4.42 respectively, P = 0.0099). There was no statistical significant difference was found in all the secondary pharmacokinetic endpoints such as Tmax, elimination rate constant and T1/2 between both the treatment groups. Dynapar QPS provides higher penetration of diclofenac in underlying tissue as compared to diclofenac gel.